Sustained censorship in QA (2026-02) (Qatar) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Qatar. Data sourced from OONI.
Censorship Incident ID: QA-2026-0122. Severity: critical. Confidence: 77%